Effect of louvered curved-baffles on thermohydraulic performance in heat exchanger tube - Jayranaiwachira, Nuthvipa; Promvonge, Pongjet; Thianpong, Chinaruk; Promthaisong, Pitak; Skullong, Sompol (My University, 2023)
The paper presents an experimental study of convection enhancement in a tube heat exchanger using louvered curved-baffle (LCB) vortex generator (VG). The heat transfer and pressure loss of air as a working fluid, flowing in an isothermal-fluxed tube were measured having Reynolds numbers (Re) between 4760 and 29,300. The LCB elements were arrayed on two tape sides in a V-shape with a 30° attack angle. At a fixed baffle height, the LCB had three axial pitch ratios (PR) from 0.5 to 1.5 and six louver angles (θ) from 0° to 90°. Thermal enhancement factor (TEF), Nusselt number (Nu), and friction factor (f) are often utilized to analyze the effect of VG geometrical variables on thermohydraulic performance. The measured results demonstrated that the LCB-inserted tube has a significantly larger Nu and f than a plain tube functioning alone, and that the Nu and f tend to rise when PR and θ decline. Using the LCB increases Nu and f by approximately 2.59-4.66 and 3.8-39.37 times, respectively. The maximal TEF is achieved for the LCB at PR = 1, θ = 45° and lower Re. Empirical correlations for Nu and f were evaluated and found to fit measured data well, with discrepancies by ± 9% and ±10%, respectively.
Keywords: Heat exchanger; Heat transfer rate; Louvered curved baffle; Thermal performance; Vortex generator